-11=w/3+-10

Simple and best practice solution for -11=w/3+-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11=w/3+-10 equation:



-11=w/3+-10
We move all terms to the left:
-11-(w/3+-10)=0
We add all the numbers together, and all the variables
-(w/3-10)-11=0
We get rid of parentheses
-w/3+10-11=0
We multiply all the terms by the denominator
-w+10*3-11*3=0
We add all the numbers together, and all the variables
-1w-3=0
We move all terms containing w to the left, all other terms to the right
-w=3
w=3/-1
w=-3

See similar equations:

| 5/3x−3=241 | | -a/6+7=-2 | | 5/4(x+5/2)=-25/8 | | b/2-3=-15 | | 53x−3=241 | | 13y^2-38y-3=0 | | p/4-5=9 | | 11+x=-x-5 | | 7b-24+2b= | | [X(x+1)})/2=276 | | (7x×6)×(9x-2)=68 | | 3x-24=7x+28 | | 4k+14=78 | | 11+x=-3x-5 | | w/15-8=-5 | | -18x+(-65)+33x=10x-9-(-6) | | 256=3^x | | 3/5x=9/70 | | 2x-50°=+10°=0 | | -42=-7+5m | | 9m–15–2m=6m–1‒m | | 9^(-4x)=15 | | 11+x=4x-5 | | 6w+8w=208 | | [x(x+1)=552 | | 3(2x–5)=2(4x+3) | | 5x-6=-4+3x+24 | | n²+n-380=0 | | 24/4(/4)=x | | X.3(2x-5)=2(3x-2) | | -u/5+13=0 | | 443.30*0.0045*99+10000000.003=b |

Equations solver categories